Big Book Media Based on Local Wisdom Batang Regency Material on Making Friends in Diversity - setyaningrum, Atika; Witanto, Yuli (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
Indonesian language in elementary school plays a vital role in developing emotions, but many students still get low learning outcomes. This is because students still have difficulty reading. This study aims to create big book media to improve the reading skills of second-grade elementary school students. The research method used is Research and Development (R&D), which uses the 8-stage development procedure of the Sugiyono model. The subjects of the study were learning media experts and learning material experts. The trial subjects were 30 students. The methods used in collecting data were observation, interviews, questionnaires, documentation and tests. The techniques used to analyze the data were qualitative, quantitative, descriptive analysis, and inferential statistics. The study's results were the assessment given by learning media experts of 93.47% (very good) and learning material experts 81.66% (very good). The results of teacher and student assessments obtained a percentage of 100% (very good). The t-test results showed a significant difference between learning outcomes in the pretest data, namely before and after using the Big Book media. Therefore, the big book media based on Local Wisdow is effective for learning Diversity Material for Grade II Elementary Schools in Batang Regency.